Eothenomys custos - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
69. Southwest China Red-backed Vole Eothenomys custos French: Campagnol sentinelle / German: Stidwestchina-Rotelmaus / Spanish: Topillo rojo de China suroccidental Other common names: Custos Oriental Vole, Southwest China Vole, Southwest Red-backed Vole Taxonomy. Microtus (Anteliomys) custos Thomas, 1912, “A-tun-tsi [= Degen Xian], N.W. Yunnan, [China].” Eothenomys custos is in the subgenus Anteliomys. Until recently it included hintoni, but this taxon is now recognized as a distinct species. Four subspecies recognized. Subspecies and Distribution. E.c.custosThomas,1912—NWYunnan(China). E.c.changsanensisWang&Yang,2000— CangMtofDaliinYunnan(China). E.c.ninglangensisWang&Li,2000—SWSichuanandNEYunnan(China). E. c. rubellus G. M. Allen, 1924 — N Yunnan (China). Descriptive notes. Head—body 79-110 mm,tail 32-50 mm; weight 21-36 g. The Southwest China Red-backed Vole is modestly sized, with relatively short tail (30-50% of head-body length) and short ears. Females have two pairs of inguinal nipples. Fur is long and soft, brown dorsally and light gray-brown ventrally. Skull is smooth, with broad interorbital region and small bullae. Molars are very similar to those of the Sichuan Red-backed Vole (FE. chinensis). Habitat. Mountain forests, bamboo stands, meadows, and stony areas at elevations of 2500-3900 m. Food and Feeding. No information. Breeding. Breeding of the Southwest China Red-backed Vole occurs from early summer to late autumn. Activity patterns. No information. Movements, Home range and Social organization. No information. Status and Conservation. Classified as [Least Concern on The IUCN Red List. Bibliography. Kaneko (1996), Lunde (2008), Luo Jing et al. (2004), Wang Yingxiang (2003), Zeng Tao et al. (2013). Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 309, DOI: 10.5281/zenodo.6707142